KUASA TUAN GURU ATAS KEPEMIMPINAN KEAGAMAAN: MODAL SOSIAL SEBAGAI LEGITIMASI PERUBAHAN SOSIAL DI LOMBOK - Zaenudin Amrulloh (Mudabbir: Jurnal Manajemen Dakwah, 2021)
Tuan Guru is a symbol of religion authorities in Lombok. The emergence of Tuan Guru in the middle of society historically is a result of political attempts, such as redeeming people from Hindu and Dutch colonialism and Islamizing Lombok people. Commonly, the reality of socio-religion of Tuan Guru is hegemony towards local society in term of dressing, behaving, and believes. Tuan Guru has great roles in mosque and Islamic boarding school. Essentially, both mosque and Islamic boarding school are platforms for Islamic culture exchanges in order to build socio-religion system in Lombok. This study applied qualitative method with critical ethnographic approach and aimed to examine the roles of Tuan Guru on social development of local society included Islamic learning groups. The study was conducted in Lombok, West Nusa Tenggara. Based on findings, the researcher found that Tuan Guru has a symbol of religion authorities in Lombok, there are mosque and Islamic boarding school. However, the current change of era made the roles of Tuan Guru failed to maintain primordial values with local society.